Gastrin and the Moderate Hypergastrinemias - Jens F. Rehfeld (International Journal of Molecular Sciences, 2021)
The antral hormone gastrin potently regulates gastric acid secretion and fundic mucosal growth. Consequently, appropriate gastrin secretion and plasma concentrations are important for the early phases of digestion. This review describes as the first premise the normal biogenesis of gastrin in the antral mucosa, but also mentions the extraantral expression. Subsequently, the molecular nature and concentration levels of gastrin in serum or plasma are overviewed. Third, assays for accurate measurements of plasma or serum concentrations are commented. Finally, the problem of moderate hypergastrinemia due to Helicobacter pylori infections and/or treatment with proton-pump inhibitors (PPI) is discussed. The review concludes that accurate measurement of the true concentrations of bioactive gastrins in plasma is important. Moreover, it suggests that moderate hypergastrinemias are also essential health issues that require serious attention.